THE INHIBITION ACTIVITY OF MIXED SODIUM MOLYBDATE-THIOUREA TOWARDS THE CARBON STEEL CORROSION IN 1% NACL SOLUTION - SIRLIYANI (NIM : 10508026); Pembimbing : Dr. Bunbun Bundjali,
In oil and gas industry, carbon steels are commonly used as a pipeline material. The presence of water, carbon dioxide (CO2) and ion such as Chlorine (Cl-) in the fluid flow accelerate the corrosion process in carbon steel pipe. One way to decrease the corrosion rate is by using the corrosion inhibitor. In this study, the use of sodium molybdate (Mo) and thiourea (TU) as a corrosion inhibitor alone and their mixes towards the carbon steel corrosion in CO2-saturated 1% NaCl solution was investigated. To get the best result, the composition of both inhibitors were varied in the 30, 45, and 60 oC temperatures. In this study, the inhibition efficiency (%IE) was measured by several methods; Wheel Test, Electrochemical Impedance Spectroscopy (EIS) and Tafel Extrapolation method. The results shows that in 60 oC temperature, 100 ppm sodium molybdate (Mo) had inhibition efficiency at 80.48% and 50 ppm thiourea (TU) had inhibition efficiency at 57.46%. For the mixture of Mo:TU (100:40 ppm) at the same temperature the inhibition efficiency was at 76.8 %. The addition of sodium molybdate in high temperature (60 oC) increased the inhibition efficiency of thiourea, on the other hand the addition of thiourea decreased the inhibition efficiency of sodium molybdate. In resume, the inhibition efficiency of the mixture of sodium molybdate-thiourea is less effective than the inibition efficiency of the sodium molybdat alone.